MENGUAK POTENSI ZAKAT DI KABUPATEN INDRAGIRI HILIR - zuraidah zuraidah (Hukum Islam, 2018)
The potential of Zakat in Indonesia is very large, as well as in Indragiri Hilir Regency. The potential of zakat in this area from the agriculture, plantation, livestock and fisheries sector is estimated to amount to ± Rp. 270.2 Billion). Especially if added to the trade and mining sectors, services, as well as wealth zakat from individuals who have always liked to pay their zakat directly to mustahik, as well as zakat fitrah and zakat mal collected by amil-amil in mosques or mushalla that have not was reported to BAZNAS. Until now, the new can be collected by BAZNAS Indragiri Hilir Regency only 0.85%. Even so, most of them come from ASN profession zakat in Indragiri Hilir Regency.